Consumer Satisfaction Level of Asri Fresh Kalamansi Syrup At Sari Rasa Gift Shop - Salsahbillah, Wulan; Yulihartika, Rika Dwi; Fariadi, Herri (Journal of Multidisciplinary Research, 2025)
Consumer satisfaction is one of the important things in marketing. If consumers feel satisfied with a product from a restaurant, generally the consumer will continue to buy and consume. The aim of this research is to determine the level of consumer satisfaction with fresh, beautiful kalamansi syrup at the Sari Rasa gift shop in Bengkulu City. Based on research on the level of consumer satisfaction with fresh, beautiful kalamansi syrup in the Sari Rasa gift shop in Bengkulu City, it can be concluded that the level of consumer satisfaction with fresh, beautiful kalamansi syrup in the Sari Rasa gift shop in Bengkulu City is going well. then the consumer satisfaction index averages 3.79 in the good category